The Effect of Using Whatsapp Social Media in Learning on Science Learning Outcomes of Grade V Students at SD Inpres Borong Jambu II Makassar City - Sari, Nur Indah; Satriawati; Khaedar, Muh. (Jurnal Mercusuar, 2022)
"This study aims to determine whether there is an Influence of Utilizing WhatsApp Social Media in Learning on the Learning Outcomes of Science for Grade V Students at SD Inpres Borong Jambu II in Makassar City. This research is classified as an experimental study with a pre-experimental design using the one-group pretest-posttest design. The sample of this study consisted of 22 students from class VA of SD Inpres Borong Jambu II in Makassar City, including 14 male students and 8 female students. The data collection techniques used in this study were tests and observation sheets. The data analysis techniques used were descriptive analysis and inferential analysis for hypothesis testing using SPSS 22 for Windows. The results of this study showed that the use of WhatsApp social media in learning had a significant effect on the learning outcomes of Science for Grade V Students at SD Inpres Borong Jambu II in Makassar City, with a significant value of 0.00 < α (0.05), meaning that H0 was rejected and H1 was accepted.